2017
DOI: 10.1007/s10900-017-0376-x
|View full text |Cite
|
Sign up to set email alerts
|

Health Behavior Regarding Cardiovascular Diseases Among Nepali Adults

Abstract: The main aim was to assess Nepali adults' knowledge, health beliefs, and health promoting behaviors regarding cardiovascular diseases (CVDs). A descriptive, cross sectional study was conducted in five wards of Lalitpur Sub-Metropolitan City. A random sample of 300 Nepali individuals aged 20-65 years completed the heart disease knowledge questionnaire and health beliefs related to cardiovascular diseases. The health belief model related to CVDs was used. Sociodemographic and personal information was collected. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…These mothers also had a greater practice of screening than mothers with low education levels, which might be due to higher-educated mothers being more conscious about their health and more aware about cervical cancer. Several studies have supported the positive relationship between education level and high knowledge in Nepali context [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…These mothers also had a greater practice of screening than mothers with low education levels, which might be due to higher-educated mothers being more conscious about their health and more aware about cervical cancer. Several studies have supported the positive relationship between education level and high knowledge in Nepali context [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with the results of most studies in this field. 34 38 The perceived benefits most frequently mentioned by both genders were related to the positive effects of hypertension control on heart and brain stroke prevention, whereas the least frequently cited perceived benefits were related to the positive effects of hypertension control on the prevention of visual impairment. Similar results were obtained by Gibson et al 39 and Ford et al 40…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes, cultural practices, health misconceptions, and myths may be barriers to healthy behavior [17]. Hence, a qualitative approach should be taken to understanding the cultural beliefs and barriers to healthy behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted in Nepal also showed that women took cardiovascular diseases more seriously than did men. This condition may be because, in Nepal, females regarded as the sole caretaker of family members; hence, they may take health issues more seriously than males do [17].…”
Section: Discussionmentioning
confidence: 99%